2005
DOI: 10.1099/vir.0.81099-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression, localization and effects on virulence of the cysteine-rich 8 kDa protein of Potato mop-top virus

Abstract: Potato mop-top virus (PMTV) RNA3 contains a triple gene block (TGB) encoding viral movement proteins and an open reading frame for a putative 8 kDa cysteine-rich protein (CRP). In this study, PMTV CRP was shown to be expressed in the course of virus infection, and a PMTV CRP-specific subgenomic RNA was mapped. CRP has previously been shown to be dispensable for infection of PMTV in Nicotiana benthamiana. In this study, PMTV CRP was found to increase the severity of disease symptoms when expressed from Potato v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 53 publications
0
34
1
1
Order By: Relevance
“…These data demonstrated that the expressed protein (p12BM) rather than the p12BM gene sequence itself suppressed PVX infection. A similar effect was observed when the CRP of potato mop-top virus was expressed from barley stripe mosaic virus (Lukhovitskaya et al, 2005a). Additionally, the inability of PVX-p12BM-stop to induce an HR implied that the p12 protein, but not the sequence encoding it, is involved in HR induction in PVX-p12-infected plants.…”
Section: Resultsmentioning
confidence: 62%
“…These data demonstrated that the expressed protein (p12BM) rather than the p12BM gene sequence itself suppressed PVX infection. A similar effect was observed when the CRP of potato mop-top virus was expressed from barley stripe mosaic virus (Lukhovitskaya et al, 2005a). Additionally, the inability of PVX-p12BM-stop to induce an HR implied that the p12 protein, but not the sequence encoding it, is involved in HR induction in PVX-p12-infected plants.…”
Section: Resultsmentioning
confidence: 62%
“…This has also been observed for other proteins with silencing suppressor activities, such as 16K of tobacco rattle virus and p14 of beet necrotic yellow vein virus [4,18]. Because the 8K protein acts as a virulence factor [13], the differences …”
mentioning
confidence: 58%
“…The fourth ORF of RNA-TGB encodes a putative cysteine-rich protein (8K protein), which appears to enhance the virulence of the virus and to act as a weak RNA silencing suppressor [13,14].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RNA3 contains four open reading frames (ORFs) predicted to encode the TGB proteins TGBp1 (51K), TGBp2 (13K), and TGBp3 (21K) and an 8K cysteine-rich protein (19)(20)(21) (Fig. 1A).…”
mentioning
confidence: 99%